Green Supply Chain Management and Its Effect on Corporate Sustainability in Manufacturing Industries (Universitas Kristen Indonesia Toraja, 2024)
This research explores the relationship between green supply chain management practices and corporate sustainability in the manufacturing sector. By analyzing survey data from 150 companies, the study identifies critical factors such as resource efficiency, waste reduction, and supplier collaboration that contribute to sustainable operations. Recommendations are provided for companies aiming to balance profitability and environmental responsibility.